Dietary Customs and Social Deprivation in an Aging Population From Southern Italy: A Machine Learning Approach - Tatoli, Rossella; Lampignano, Luisa; Donghia, Rossella; Castellana, Fabio; Zupo, Roberta; Bortone, Ilaria; De Nucci, Sara; Campanile, Giuseppe; Lofù, Domenico; Vimercati, Luigi; Lozupone, Madia; De Pergola, Giovanni; et al. (Frontiers in Nutrition, 2022)
Background: Diet and social determinants influence the state of human health. In older adults, the presence of social, physical and psychological barriers increases the probability of deprivation. This study investigated the relationship between social deprivation and eating habits in non-institutionalized older adults from Southern Italy, and identified foods and dietary habits associated with social deprivation. Methods: We recruited 1002 subjects, mean age 74 years, from the large population-based Salus in Apulia Study. In this cross-sectional study, eating habits and the level of deprivation were assessed with FFQ and DiPCare-Q, respectively. Results: Deprived subjects (n=441) were slightly more females, slightly older and with a lower level of education. They consumed less fish (23 g vs 26 g), fruiting vegetables (87 g vs 102 g), nuts (6 g vs 9 g) and less “ready to eat” dishes (29 g vs 33 g). A Random Forest (RF) model was used to identify a dietary pattern associated with social deprivation. This pattern included increased consumption of low-fat dairy products and white meat, and a decreased consumption of wine, leafy vegetables, seafood/shellfish, processed meat, red meat, dairy products and eggs. Conclusion: The present study showed that also in areas of the Mediterranean Sea social deprivation and diet is associated with a tendency to consume less healthy foods.